Profil capaian Technological, Pedagogical, and Content Knowledge (TPACK) mahasiswa tahun kedua calon guru matematika - Fahira, Popy; Putra, Aan (IKIP Siliwangi, 2024)
Prospective teachers must possess strong knowledge of technology, pedagogy, and mathematical content to ensure optimal learning outcomes. Therefore, mathematics teacher candidates are equipped with knowledge of technology, pedagogy, and content through various courses. However, the effectiveness of these courses in enhancing Technological, Pedagogical, and Content Knowledge (TPACK) must be regularly assessed as part of the evaluation process for teacher education programs. This study aims to describe the TPACK achievement of second-year mathematics teacher candidates. The research is a survey study involving 18 second-year mathematics education students at a university in Jambi, Indonesia. A TPACK questionnaire comprising 7 components with a total of 35 items was used. Interviews with program coordinators were conducted to enrich the data on curriculum content designed to support students’ TPACK development. The results indicate that the students’ mastery of TPACK is not yet optimal. The university needs to further optimize TPACK mastery through courses or extracurricular activities during the remaining period of study.